The spectre of Islamic terrorism: comparative insights : a machine-generated literature overview - Solomon, Hussein (Palgrave Macmillan, 2024)
This book presents the result of an innovative challenge, to create a systematic literature overview driven by machine-generated content. It examines Islamic terrorism perpetrated by different organizations in different regional and global settings, including Al Qaeda and Islamic State or ISIS, Afghanistan’s Taliban, Lebanon’s Hezbullah and Nigeria’s Boko Haram. The author examines the ability of these organizations to transform themselves and survive despite a plethora of counter-terrorism measures, and to continuously adapt by inserting themselves into regional conflicts, exploiting sectarian tensions, and finding new resonance of their messaging to potential recruits. The chapters in this volume provide clear insights into terrorism - its origins, trajectories, and ways in which the spectre of Islamic terrorism can be defeated. Hussein Solomon is Senior Professor of Gender and Africa Studies at the University of the Free State, South Africa.